(untitled) (Journal of Applied Membrane Science & Technology, 2022)
Seawater desalination and water recovery from wastewater are potential solutions to meet the ever-growing water demand. Membrane distillation (MD) is a next-generation membrane technology that can be harnessed for sustainable water production. The advantages of the MD process and the various operating configurations are discussed. The challenges in membrane development are highlighted, and the various state-of-the-art approaches for improving membrane performance, fouling resistance, anti-wetting character, and minimizing concentration/temperature polarisations are included. The process design is another crucial aspect of the successful implementation of the MD. Response surface methodology and Analysis of Variance (ANOVA) have been explored to identify the optimal operating conditions. Machine learning and computational fluid dynamics analysis (CFD) that have been used to predict the performance and influence of the process parameters are discussed. The energetics and economics of the MD process have also been discussed. The MD process could become sustainable if it utilizes renewable energy sources (solar, geothermal) for bulk heating of the feed. This article highlights the various challenges associated with MD technology and provides an overview of the strategies researched to overcome them.